A stellar tidal stream around the Whale galaxy, NGC 4631 - Martínez-Delgado, David; D'Onghia, Elena; Chonis, Taylor S.; Beaton, Rachael L.; Teuwen, Karel; GaBany, R. Jay; Grebel, Eva K.; Morales, Gustavo (The astronomical journal, 2015)
We report the discovery of a giant stellar tidal stream in the halo of NGC 4631, a nearby edge-on spiral galaxy interacting with the spiral NGC 4656, in deep images taken with a 40 cm aperture robotic telescope. The stream has two components: a bridge-like feature extending between NGC 4631 and NGC 4656 (streamSE) and an overdensity with extended features on the opposite side of the NGC 4631 disk (streamNW). Together, these features extend more than 85 kpc in projection. The orientation of streamSE relative to the orientations of NGC 4631 and NGC 4656 is not consistent with an origin from an interaction between these two spirals, and is more likely debris from a satellite encounter. The stellar tidal features can be qualitatively reproduced in an N-body model of the tidal disruption of a single, massive dwarf satellite on a moderately eccentric orbit (e = 0.6) around NGC 4631 over ∼3.5 Gyr. Both modeling and inferences from the morphology of the streams indicate these are not associated with the complex HI tidal features observed between both spirals, which likely originate from a more recent, gas-rich accretion event. The structure of streamNW suggests that it may contain the progenitor of the stream, in agreement with the N-body model. However, we cannot exclude other possibilities such as the satellite dwarf galaxy NGC 4627 being the progenitor based on these data. In addition, streamNW is roughly aligned with two very faint dwarf spheroidal candidates. The system of dwarf galaxies and the tidal stream around NGC 4631 can provide an additional interesting case for exploring the anisotropy distribution of satellite galaxies recently reported around Local Group spiral galaxies by means of future follow-up observations.